Aktual'nyi ob"ektiv . Aktual'nyi ob"ektiv . Focus . Актуальный объектив - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Television premiere of the documentary "In the Light of Day." Contributors: Bakaev, Kh. (Director); Tashov, A. (Camera) Премьера телевизионного документального фильма "При свете дня". Создатели: Бакаев, Х. (Режиссер); Ташов, А. (Оператор)